Inter/Multimedial Constructions of Islam in Post-9/11 TV Series: The West Wing and 24 - Brigitte Georgi-Findlay (European Journal of American Studies)
Since The West Wing (NBC, 1999-2006), the political drama series has been a proliferating format for fictional engagements with American politics. Georgi-Findlay focuses on how The West Wing and 24 (Fox, 2001-2010) engage public narratives about Islam and Islamophobia, arguing that the shows go beyond what Evelyn Alsultany has termed “simplified complex representations” by creating contradictory, multivocal texts that display dynamics of internal disaccord. Representations of Arabs, Muslims and Muslim countries are embedded within storylines that challenge each other. Especially The West Wing stages discussions that can lead to informed debates, reflecting and exposing the contradictions within the American national identity discourse between an inclusionist civic and an exclusionist racialized nationalism. In both series, polyvocal narratives are brought across not only by intertwining multiple discourses, but also by way of aesthetic strategies and intermedial references that supply additional textual layers, complicating viewers’ processes of meaning-making and contributing to in-text dissensus and ideological ambivalences. Both series thus can be read against the grain, as contradictory, multivocal texts that both reflect and expose Islamophobia.